Electrophysiological Assessment and Classification of Motor Pathway Function in Patients With Spinal Dural Arteriovenous Fistula. Issue 1 (January 2019) - Nakanishi, Kazuyoshi; Tanaka, Nobuhiro; Fujimoto, Yoshinori; Nishikawa, Koichiro; Kamei, Naosuke; Nakamae, Toshio; Kotaka, Shinji; Adachi, Nobuo
Abstract : Purpose: The diagnosis of spinal dural arteriovenous fistula (SDAVF) is difficult and often delayed because clinical features are often nonspecific. We assessed the motor function electrophysiologically in patients with SDAVF. Methods: Motor-evoked potentials after transcranial magnetic stimulation and compound muscle action potentials and F-waves after electrical stimulation in the ulnar and tibial nerves were measured from the abductor hallucis (AH) muscles in 14 patients with SDAVF (SDAVF group), 12 patients with compressive thoracic myelopathy (CTM group), and 16 normal subjects (control group). The peripheral conduction time determined from abductor hallucis muscles (PCT-AH) and the central motor conduction time determined from abductor hallucis muscles (CMCT-AH) were calculated. According to the neurological findings, patients in the SDAVF group were classified to upper motor neuron (UMN) sign and lower motor neuron (LMN) sign categories. Results: CMCT-AH in the SDAVF and CMT groups were significantly longer than those in the control group. PCT-AH in the SDAVF group was significantly longer than that in the control and CMT groups. Twelve patients in the SDAVF group showed abnormal CMCT-AH and/or PCT-AH. Abnormal CMCT-AH and PCT-AH were detected in five cases that exhibited UMN sign and/or LMN sign. Three cases with abnormal CMCT-AH and normal PCT-AH exhibited UMN sign. LMN sign without UMN sign was observed in four cases with abnormal PCT-AH and normal CMCT-AH. Conclusions: Our study revealed abnormalities in the corticospinal tract and/or lower motor neurons, and classified the patients with SDAVF into three types: the UMN type, LMN type, and mixed type.